Actividad alexitera de Tabernaemontana sananho Ruiz & Pav. (Kunapi) y Minthostachys cf. mollis (kunth) Griseb (Kurarina) sobre el veneno de Bothrops atrox (“Pitalala”) - León Cárdenas, Karen Priscila (2017)
Ecuador has abundant and diverse flora and fauna in its four geographic regions. In the Ecuadorian Amazon inhabits the snake Bothrops atrox, that caused the highest number of accidents by bites registered; inhabitants of this region ensure that plants such as Kunapi (Tabernaemontana sananho Ruiz & Pav) and Kurarina (Minthostachys mollis (kunth) Griseb) are commonly used to counteract said effect. In this investigation, it was determined in vitro the neutralizing activity of the extracts of these two-plant species on the effects of the venom of B. atrox. The Samples of these plants were collected in Huamboya and Morona, cantons of the province of Morona Santiago, from which, were prepared dry total extracts, alcoholic and aqueous to test the anti-coagulant activity and anti-proteolytic, using different concentrations of the extracts on a defined dose of the venom of B. atrox; in addition, the electrophoretic profile was determined, before and after the action of the extracts. The results obtained from anticoagulant activity revealed that a concentration of 0,25 ppm of the alcoholic extract of both species is sufficient to neutralize the coagulant effect of a dissolution 0.02 mg/ml, of poison by increasing the clotting time of the plasma by 500%. The results of anti-proteolytic activity evidenced that the aqueous extract of T. Sananho was more effective and that M. mollis does not have this activity. The electrophoretic profile determined that the alcoholic extracts of the two-species changed the protein profile by the appearance of a band for a protein of 45,8 kDa.